Enhanced Phytoextraction Technologies for the Sustainable Remediation of Cadmium-Contaminated Soil Based on Hyperaccumulators—A Review - Xuerui Cao; Qing Dong; Lihui Mao; Xiaoe Yang; Xiaozi Wang; Qingcheng Zou (Plants)
Heavy metal pollution in soil is a significant challenge around the world, particularly cadmium (Cd) contamination. In situ phytoextraction and remediation technology, particularly focusing on Cd hyperaccumulator plants, has proven to be an effective method for cleaning Cd-contaminated agricultural lands. However, this strategy is often hindered by a long remediation cycle and low efficiency. To address these limitations, assisted phytoextraction has been proposed as a remediation strategy based on the modification of certain traits of plants or the use of different materials to enhance plant growth and increase metal absorption or bioavailability, ultimately aiming to improve the remediation efficiency of Cd hyperaccumulators. To thoroughly understand the progress of Cd hyperaccumulators in remediating Cd-polluted soils, this review article discusses the germplasm resources and assisted phytoextraction strategies for these plants, including microbial, agronomic measure, chelate, nanotechnology, and CO2-assisted phytoextraction, as well as integrated approaches. This review paper critically evaluates and analyzes the numerous approaches and the remediation potential of Cd hyperaccumulators and highlights current challenges and future research directions in this field. The goal is to provide a theoretical framework for the further development and application of Cd pollution remediation technologies in agricultural soils.